A private affair - Lokko, Lesley (Orion Books, 2012)
Sam is the ugly duckling who grew into a swan. Now beautiful and wealthy, with a glittering career, no one can understand why she's still on her own. When she meets a handsome stranger on holiday, things finally seem to be falling into place. Meagan is a true survivor. The teenage runaway who worked her way off the streets, she was swept off her feet by Tom, a young army officer, to live on the other side of the world, finally escaping the family she loathed. Dani is the beautiful misfit, desperately looking for daddy in all the wrong places, and finding instead a man who will teach her everything that is wrong and corrupt about love. And Abby is the model wife, everything her husband and family could want, and more, but never being herself-until a dark secret threatens to pull her well-ordered life apart. A Private Affair is the new spellbinding tale of love and friendship, glamour and guilt from bestselling author Lesley Lokko.